2022
DOI: 10.1371/journal.pntd.0010190
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices regarding schistosomiasis infection and prevention: A mixed-methods study among endemic communities of western Uganda

Abstract: Introduction In Uganda, schistosomiasis (re)infections have continued to remain high despite the implementation of mass drug administration and sensitization campaigns aimed at controlling the disease. This could imply that there are some barriers to the implemented preventive measures. We conducted a mixed-methods study in Kagadi and Ntoroko districts around Lake Albert to assess knowledge, attitudes, and practices regarding schistosomiasis and to explore and understand perspectives regarding the disease. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 27 publications
5
31
1
Order By: Relevance
“…However, our research contrasts with a study in Ghana that found no signi cant association between proper diagnosis and health service utilization [5]. This could be because of variations in the level of knowledge about the disease reported by studies which reveal inadequate knowledge about the diagnosis of schistosomiasis by communities in Uganda [30], and health seeking [42]. Re ning knowledge of MDA and addressing issues of side effects could improve health seeking from modern sources [28].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, our research contrasts with a study in Ghana that found no signi cant association between proper diagnosis and health service utilization [5]. This could be because of variations in the level of knowledge about the disease reported by studies which reveal inadequate knowledge about the diagnosis of schistosomiasis by communities in Uganda [30], and health seeking [42]. Re ning knowledge of MDA and addressing issues of side effects could improve health seeking from modern sources [28].…”
Section: Discussioncontrasting
confidence: 82%
“…Although the PZQ uptake has been increasing steadily over the years, the inconsistency attributed to funding gaps is likely to affect the achievement of the WHO target [29]. Moreover, endemic communities continue to engage in risky water, sanitation, and hygiene (WASH) practices [30,31]. This also implies that such communities must receive constant treatment to contain the spread of the disease and control morbidity levels.…”
Section: Research Gapsmentioning
confidence: 99%
“…Thus, whoever has acquired sufficient knowledge on schistosomiasis transmission would take cognisance of This study is, however, in contrast with a study carried out in Uganda [25] to assess knowledge, attitudes, and practices regarding schistosomiasis infection and prevention, where a total of 98.5%, 81.3%, and 78.5% had heard about schistosomiasis and knew the main transmission modes and symptoms respectively. The good knowledge recorded in the study was attributed to countrywide health education campaigns organized by the Ministry of Health between 2017 and 2018.…”
Section: Discussionmentioning
confidence: 91%
“…Even though some people do not drink from the lake, they depend on lake water for all other water activities. Research in Western Uganda also shows that schistosomiasis was considered hard to prevent because the lake is the only source of free water [63] and many other Ugandan studies highlight a lack of safe water in fishing communities [49,[63][64][65]. The taps available in Musubi and Bugoto villages were unreliable, they frequently broke down, some were faulty or locked and on cloudy or rainy days the taps run out of water because they used a solar pump.…”
Section: Discussionmentioning
confidence: 99%